TURKEY’S POSİTİON ON THE BEGİNNİNG OF THE IRAQ-IRAN WAR 22 SEPTEMBER 1980 - Merkhan, Hozan Suliman; Saleem, Hajeen Kamal (Journal of Duhok University, 2018)
The Iraq-Iran war, which began on September 22, 1980, is considered as one of the longest wars in the Middle East in the 20th century. This war has left great and direct effects on Turkey because it has common borders with the two warring states. The significance of the study comes from the fact that it examines the Turkish position since the Iraq-Iran war started. The study becomes more important because of the geographical location of these three countries to Kurdistan region -Iraq, as the political movements in these countries reflected negatively and positively on Kurdistan region. Consequently, it is our duty to follow the history of these countries and study everything related to them. The study tries to raise a number of questions regarding the Turkish position on the beginning of the war. Such questions include how was the position of official Turkish and the media towards the war? Which country was accused by Turkey of being the aggressor and the initiator of the war? And how were the statements of Turkish officials about that war? The economic factor, which had a significant impact on Turkey’s position on the war, was also discussed in this study.